Supplemental damages in private international law : the awarding of interest, attorneys' fees and costs, punitive damages and damages in foreign currency examined in the comparative and international context /: the awarding of interest, attorneys' fees and costs, punitive damages and damages in foreign currency examined in the comparative and international context. (1998) - Unknown
No abstract available